Pengaruh Kualitas Pelayanan dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan (Studi Kasus di "Nyaman Konveksi") - Widodo, Hanif Wahyu; Drs. Sri Padmantyo, M. B. A. (2016)
The purpose of this study was to determine the effect of service quality on customer loyalty and satisfaction as moderator variables that exist in Pleasant Convection in Blora. It is hoped the study was able to find a significant relationship between the three variables that exist and to be a view for future researchers. In this research there to influential hypothesis Service Quality customer satisfaction, customer satisfaction to loyalty, as well as the quality of services to loyalty. The population of this study takes on the part of those who have used the services of a comfortable convection. This study uses a sampling technique by taking a sample of 50 respondents for. This study using multiple linear regression (t test, F Test,R^2Test). This study resulted in several findings including service quality variables significant positive effect on customer satisfaction. Variable customer satisfaction significant positive effect on customer loyalty.influence service quality variables positively on customer loyalty. the variable quality of service and customer satisfaction together (simultaneously) significantly affects customer loyalty.